The Treatment Of Coal With Oil And Other Petroleum Products - J. M. Pilcher (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1939)
The application of oil to coal for-the reduction of dust has greatly increased the consumers' satisfaction with solid fuels, especially those for domestic use. The combination of oil-treated coal and automatic firing by a small stoker has made possible clean, automatic heating with bituminous coal. This, with the added pressure of competition by other fuels, has caused a rapid development of oil treating practice. A variety of materials derived" from petroleum oils is available from which one may choose for treating a par-ticular coal. Until recently, however, little information had been published to guide the choice. It is most im-portant that the proper type and amount of oil be used in order that all coals marketed as "dustless" will be reason-ably dustless, and thereby maintain a good reputation for oil-treatment. During the past two and one-half years, an investigation of a number of the problems related to the treatment of coal with oil has been conducted at Battelle Memorial Institute. This project was jointly sponsored by Bituminous Coal Research. Inc., Standard Oil Company of New Jersey, Sun Oil Company, and Viking Manufacturing Company. A progress report giving the principal results of the work of the first year was presented before the American Society of Mechanical Engineers in December 1937.1 The present paper is a summary of the entire inves-tigation.